Antioxidant potential of blackberry extract: integrated in vitro, in vivo and in silico molecular docking analysis - Komisarenko, Mykola; Marchenko, Artem; Maslov, Oleksandr; Lebedinets, Iryna; Yudkevych, Tetiana; Kolisnyk, Sergii; Koval, Alla (The Ukrainian Scientific Medical Youth Journal, 2026)
in recent years, increasing attention has been paid to natural compounds as potential therapeutic agents due to their broad spectrum of biological activities. Plant-derived compounds with antioxidant properties are of particular interest, as they may suppress pathological pathways. Therefore, the search for novel natural compounds capable of attenuating oxidative stress remains a promising area of biomedical research. The aim of this work was to evaluate the antioxidant potential of a thick blackberry fruit extract using in vitro, in vivo, and in silico molecular docking models. The study investigated a thick blackberry fruit extract. Docking simulations were performed using AutoDockTools 1.5.6. The antioxidant potential was assessed in vitro by the ferric reducing antioxidant potential (FRAP) assay, potentiometric method, and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay; in vivo, on mice via a carrageenan-induced paw edema assay. The in silico evaluation of antioxidant properties indicated that the major blackberry anthocyanins—cyanidin-3-glucoside, cyanidin-3-(3''-malonyl glucoside), and cyanidin-3-xyloside—blocked two out of three prooxidant targets. In contrast, cyanidin-3,3'-diglucoside and cyanidin-3-rutinoside blocked only one out of three targets, namely xanthine oxidoreductase. In vivo experiments revealed that administration of blackberry thick fruit extract at doses of 60.0 and 120.0 mg/kg possessed high antioxidant potential, where the extract significantly increased catalase levels to 51.31 ± 3.00 and 70.56 ± 3.40 μmol/min·L and decreased malondialdehyde (MDA) levels to 0.140 ± 0.016 and 0.120 ± 0.016 μmol/L in serum compared with the control group, respectively. Antioxidant profiling showed that the blackberry fruit extract exhibited the highest activity in the FRAP, potentiometric, and ABTS assays. According to the theoretical results, it was shown that due to the high content of anthocyanins in the blackberry fruit extract, the extract possesses the ability to inhibit crucial prooxidant enzymes. In vivo and in vitro models showed that the blackberry fruit extract demonstrated predicted interactions with enzyme targets relevant to oxidative stress.